2019
DOI: 10.1109/access.2019.2925812
|View full text |Cite
|
Sign up to set email alerts
|

Window Zooming–Based Localization Algorithm of Fruit and Vegetable for Harvesting Robot

Abstract: Localization of fruit and vegetable is of great significance to fruit and vegetable harvesting robots and even harvesting industries. However, uncontrollable factors, such as varying illumination, random occlusion, and various surface color and texture, constrain the localization of fruit and vegetable using the vision imaging technology under unconstructed environment. Our previous studies have developed various methods (illumination normalization, features-based classification, etc.) to localize a certain ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…More recently, Wang et al [6] proposed an improvement in the methods of fruit localization for harvesting robots using binocular stereo images. The proposed method uses the Faster region-based convolutional neural network (R-CNN), which is able to achieve a recognition rate of 96.33% in six different conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Wang et al [6] proposed an improvement in the methods of fruit localization for harvesting robots using binocular stereo images. The proposed method uses the Faster region-based convolutional neural network (R-CNN), which is able to achieve a recognition rate of 96.33% in six different conditions.…”
Section: Methodsmentioning
confidence: 99%
“…These can include spaceborne, airborne and terrestrial platforms, with applications in crop monitoring, water management, fertigation, harvesting, and decision making in general. In particular, using automated or semi-automated harvesting methods is not only economically cost effective, but also more efficient than traditional methods, and significantly reduces the harvest More recently, Wang et al [6] proposed an improvement in the methods of fruit localization for harvesting robots using binocular stereo images. The proposed method uses the Faster region-based convolutional neural network (R-CNN), which is able to achieve a recognition rate of 96.33% in six different conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koirala et al [38] proposed the MangoYOLO network for real-time detection of mangoes in orchards with high accuracy and in real time. Wang et al [39] used the Faster Region-based Convolutional Neural Network (R-CNN) model to identify fruits and vegetables. Gao et al [40] proposed an apple detection method based on a fast regional convolutional neural network for multiclass apple dense fruit trees.…”
Section: Introductionmentioning
confidence: 99%
“…A 93.7% success rate of detection was yielded for fruit calyxes, and a 92% success rate was yielded for the correct segregation of fruits during nighttime with flash. In [17], two CCD color cameras integrated with a window zooming-based algorithm were utilized to locate multiple fruits and vegetables. The results showed that under varying illumination and partially occluded circumstances, the localization errors were less than 7.5 mm for a measuring distance of 300-1600mm.…”
Section: Introductionmentioning
confidence: 99%